Numerical simulation of a cubical cavity filled with oil showing temperature-dependent viscosity - Córdoba Estrada, Paola Andrea (2014)
We performed a numerical and experimental study of laminar natural convection flow in an oil filled cubical cavity. The fluid is a dielectric oil used for cooling distribution and power transformers. This fluid has temperature-dependent viscosity. The cubical cavity of interest has an imposed temperature difference between two opposite vertical walls while the other walls are insulated. The cavity dimensions are 0.1m x 0.1m x 0.1m were a flow with a characteristic Rayleigh number Ra = 1.7 × 108 was obtained. The numerical study was carried out by applying the Finite Element Method to solve the 3D Navier-Stokes and heat equations using the in-house developed Par-GPFEP code. The influence of the temperature viscosity dependence on total heat transferred and the flow pattern have been evaluated. An experimental setup was developed to validate the numerical results. The temperature profiles in the vertical mid-axis at mid-plane of the cavity were measured and compared with the numerical results. We found reasonable agreement between numerical simulations and experimental measurements. Although there are several studies of the flow in a square cavity in this configuration, there is limited information in the literature regarding 3D flow in cubical cavities with variable properties of the working fluid. This work provides numerical and experimental data in this wide unexplored problem that can be used as benchmark to validate CFD models as well as to understand how to optimize devices based on natural convection cooling processes.